The Impact of Motivation and Work Environment in Improving the Performance of Government Employees of the Hiliran Gumanti Sub-District, Solok Regency - Rivo Revanda; Afni Yeni; Wahyu Indah Mursalini (CV. Proaksara Global Transeduka, 2025)
The role of employee performance in organizational effectiveness is of particular importance in the public sector, where success in service delivery is critically based on human resources. Yet, many of the government institutions struggle in ensuring peak performance by their employees due to low motivation and lesser conducive workplaces environment. They can create obstacles to productivity, slow down the processes, and eventually affect the quality of public services. This study was carried out in Hiliran Gumanti District within Solok Regency to examine how motivation and workplace conditions affect the job performance of government workers. The researchers used a quantitative approach and conducted surveys using questionnaires to assess the relationships. The findings revealed that the motivation factor positively and significantly influences job performance, and therefore the alternative hypothesis is accepted. Similarly, work environment also significantly influenced employee performance, therefore, alternative hypothesis was also accepted. Moreover, results of joint analysis found that motivation and work environment together have significant effect on employee performance, which strengthens conclusion that both motivational and work environment have critical role on increasing the effectiveness of government employees.